Getting a networking job for dummies - Gregory, Peter H.; Hughes, Bill 1960- (John Wiley & Sons, 2015)
This book offers all the tools and step-by-step guidance you need to stand out from the crowd, get your foot in the door, and secure a job in the computer-networking. In no time, you'll get a handle on networking roles, necessary education, training, and certifications, ways to brand yourself for your dream career, and more.
Includes index. - Print version record
Keywords: Telecommunication -- Vocational guidance; Computer networks -- Vocational guidance; Télécommunications; Orientation professionnelle; Réseaux d'ordinateurs; Orientation professionnelle; Computer networks; Vocational guidance; Telecommunication; Vocational guidance